Novel peptide-based vaccine targeting heat shock protein 90 induces effective antitumor immunity in a HER2+ breast cancer murine model. Issue 9 (15th September 2022) - Kang, Jinho; Lee, Hye-Jin; Lee, Jimin; Hong, Jinhwa; Hong Kim, Yeul; Disis, Mary L; Gim, Jeong-An; Park, Kyong Hwa
Abstract : Background: Heat shock protein 90 (HSP90) is a protein chaperone for most of the important signal transduction pathways in human epidermal growth factor receptor 2-positive (HER2+) breast cancer, including human epidermal growth factor receptor 2, estrogen receptor, progesterone receptor and Akt. The aim of our study is to identify peptide-based vaccines and to develop an effective immunotherapeutics for the treatment of HER2+ breast cancer. Methods: HSP90-derived major histocompatibility complex (MHC) class II epitopes were selected using in silico algorithms and validated by enzyme-linked immunospot (ELISPOT). In vivo antitumor efficacy was evaluated in MMTV neu -transgenic mice. HSP90 peptide-specific systemic T-cell responses were assessed using interferon gamma ELISPOT assay, and immune microenvironment in tumors was evaluated using multiplex immunohistochemistry and TCRβ sequencing. Results: First, candidate HSP90-derived MHC class II epitopes with high binding affinities across multiple human HLA class II genotypes were identified using in silico algorithms. Among the top 10 peptides, p485 and p527 were selected as promising Th1 immunity-inducing epitopes with low potential for Th2 immunity induction. The selected MHC class II HSP90 peptides induced strong antigen-specific T cell responses, which was induced by cross-priming of CD8 + T cells in vivo. The HSP90 peptide vaccines were effective in the established tumor model, and their efficacy was further enhanced when combined with stimulator of interferon genes (STING) agonist and/or anticytotoxic T lymphocyte-associated antigen-4 antibody in MMTV neu -transgenic mice. Increased tumor rejection was associated with increased systemic HSP90-specific T-cell responses, increased T-cell recruitment in tumor microenvironment, intermolecular epitope spreading, and increased rearrangement of TCRβ by STING agonist. Conclusions: In conclusion, we have provided the first preclinical evidence of the action mechanism of HSP90 peptide vaccines with a distinct potential for improving breast cancer treatment.